Relationship between core muscles oxygen saturation and gross efficiency during cycling - Osaki, Ryo; Takahashi, Hideyuki (International Journal of Sports Medicine)
This study examined the muscle oxygen saturation profiles of core and thigh muscles during cycling and investigated their relationship with gross efficiency across various cycling intensities. Eleven male cyclists and triathletes performed a graded exercise test on a cycle ergometer. Muscle oxygen saturation was measured in the vastus lateralis, biceps femoris long head, erector spinae, and external oblique muscles at each intensity level, along with gross efficiency. The percentage of peak power output at which muscle oxygen saturation began to deoxygenate significantly decrease from the initial load was 60% in the vastus lateralis, 80% in the biceps femoris long head, and 70% in both the erector spinae and external oblique muscles (P < 0.05 or P < 0.01). In contrast, no significant differences in deoxygenation between muscles were observed at intensities between 60% and 90% of peak power output. At 80% of peak power output, a significant positive correlation was found between gross efficiency and oxygen saturation in the erector spinae (r = 0.745, P < 0.01). In conclusion, the oxygen saturation profile of core muscles are comparable to those of thigh muscles, and oxygen saturation in the erector spinae may contribute to gross efficiency during high-intensity cycling.